A balanced dietary - Stevens, Blanche (My University, 1905)
Introduction: The table board of Mr. Lynch Failyer furnished the foundation for this theses. During the month of April, I kept account of all food bought, the prices; of the waste; and the menus. The number who ate there that month were thirteen, eight women and five men. Their occupations were as follows- one chief cook- one assistant cook, one high school girl, five women students and five men students. The amount of food consumed equaled 1461.75 pounds. The amount wasted was 19.87 pounds. The cost of food material used, amounted to $57.33. The bulletin used for my calculations was the bulletin on the chemical composition of American foods, by W. O. Atwater and A. P. Bryant. The text book consulted was Hutchinson’s Food and Dietetics. The amount of food required to meet the daily need of the body may be represented in three different ways: 1st. In terms of potential energy: i.e., calories. 2nd . In terms of the most important chemical elements which it contains, i.e., nitrogen and carbon. 3rd. In terms of the nutritive constituents i.e., proteid, fat and carbohydrate.
A boarding-house dietry
Citation: Stevens, Blanche. A balanced dietary. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Dietaries and dietary studies; Necessity for Mixed Diet; Theses; Manuscripts (documents)